Il concetto di «capitalismo di Stato» in Lenin - Giacché, Vladimiro (——— Materialismo Storico ——— Rivista di filosofia, storia e scienze umane, 2018)
This essay is focused on uses and evolution of the concept of “State capitalism” in Lenin’s thought, from his pre-revolutionary works to the writings that led the birth of Soviet power and the first years of its consolidation. It is argued that “State capitalism”, initially built on some characters of German war economy, changes its meaning in Lenin’s late works: here it’s used to describe the specific economic pattern through which Russia should be funneled in order to promote a quick transition from little production to socialism, following the seizure of State power and the control over the main means of production by the working class party. Therefore “State capitalism” can be seen as a constitutive part of the broader concept of “transitional society”. Keywords: State capitalism; Lenin; Capitalism; Socialism; Soviet power.